Validation of SABER v2.0 Operational Temperature Data With Ground‐Based Lidars in the Mesosphere‐Lower Thermosphere Region (75–105 km). Issue 17 (12th September 2018) - Dawkins, E. C. M.; Feofilov, A.; Rezac, L.; Kutepov, A. A.; Janches, D.; Höffner, J.; Chu, X.; Lu, X.; Mlynczak, M. G.; Russell, J.
Abstract: The National Aeronautics and Space Administration (NASA) Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) Sounding of the Atmosphere using Broadband Radiometry (SABER) instrument performs near‐global measurements of the vertical kinetic temperature ( T k ) profiles and volume mixing ratios of various trace species (including O3, CO2, and H2 O), with data available from 2002 to present. In this work, the first comparative study of the latest publically available SABER version 2.0 operational retrieval is reported in order to assess the performance of satellite T k profiles relative to high‐resolution ground‐based lidar profiles. Collocated multiyear seasonal average T k profiles were compared at nine different locations, representing a variety of different latitudes. In general, the SABER v2.0 and lidar mean seasonal T k profiles agree well, with the smallest absolute values of Δ T k ( z ) (SABER minus lidar) found between 85 and 95 km, where the respective SABER and lidar uncertainties were smallest. At altitudes ≥100 km, the SABER T k ( z ) typically exhibited warmer temperatures relative to the lidar T k ( z ) profiles, whereas for altitudes ≤85 km, SABER T k ( z ) was cooler. Relative to lidar, SABER tends to exhibit a warm bias during high‐latitude summertime, with the reasons for this currently still unclear. Overall, SABER was able to reproduce the general latitude‐ and season‐specific variations in the lidar T k profiles and shown to be statistically similar for most seasons, at most locations, for the majority of altitudes, and with no overall bias. Key Points: The first comparative study of SABER version 2.0 operational temperature retrieval product with high‐resolution ground‐based lidar profiles A comparison of collocated multiyear seasonal average temperatures at nine locations (low, middle, and high latitudes) is presented An overall agreement for SABER and lidar data sets, but the presence of relative SABER warm bias during polar summer requires further investigation